The EPIC Nitinol Stent System in the Treatment of Iliac Artery Lesions: One-Year Results From the ORION Clinical Trial. (April 2014) - Clair, Daniel G.; Adams, Julie; Reen, Bernard; Feldman, Robert; Starr, Jean; Diaz-Cartelle, Juan; Dawkins, Keith D.
Purpose: To report the 1-year results of a pivotal study for a new-generation nitinol stent for the treatment of iliac atherosclerotic lesions. Methods: The ORION trial ( ClinicalTrials.gov identifier NCT00896337) was a single-arm, non-randomized, prospective, multicenter clinical trial that enrolled 125 patients (81 men; mean age 61.1±9.3 years) implanted with the EPIC self-expanding nitinol stent system in 166 de novo or restenotic iliac artery lesions ≤13 cm long. The primary endpoint was the 9-month major adverse event rate [i.e., device- or procedure-related death within 30 days, myocardial infarction during the index hospitalization, target vessel revascularization (TVR), or index limb amputation]. Follow-up occurred at hospital discharge and at 1, 9, and 12 months. An independent core laboratory evaluated ultrasound results at 1, 9, and 12 months. Results: The primary endpoint met the prespecified performance goal, with only 3.4% (4/117) of patients experiencing a major adverse event by 9 months (p<0.0001). By 12 months, 6 (5.4%) of 111 patients had TVR; none had an index limb amputation. The ankle-brachial index, Walking Impairment Questionnaire, and Rutherford classifications all showed sustained improvements through 12 months. Primary patency was 94.4% with comparable results for lesions classified as complex (TASC II C/D 95.5%) or non-complex (TASC II A/B 95.0%). Conclusion: The EPIC stent system demonstrated safety and effectiveness through 12 months, including improvements for complex lesions. The EPIC stent is a viable alternative to surgery for patients with either complex or non-complex lesions.